Genocide as Social Practice Reorganizing Society under the Nazis and Argentina's Military Juntas - Feierstein, Daniel (Rutgers University Press, 2014)
Genocide not only annihilates people but also destroys and reorganizes social relations, using terror as a method. In Genocide as Social Practice, Argentinean social scientist Daniel Feierstein looks at the policies of state-sponsored repression pursued by the Argentine military dictatorship against political opponents between 1976 and 1983 and those pursued by the Third Reich between 1933 and 1945. He finds similarities, not in the extent of the horror but in terms of the goals of the perpetrators.
Description based on print version record.
KU Select 2016 Backlist Collection
Keywords: Political Science / Human Rights; Political science; Electronic books